2008
DOI: 10.1152/ajpgi.00581.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by growth hormone of HNF-6-regulated hepatic genes, a potential mechanism for improved liver repair during biliary injury in mice

Abstract: activation by growth hormone of HNF-6-regulated hepatic genes, a potential mechanism for improved liver repair during biliary injury in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…6). As expected from our laboratory's previous work in GH-treated liver (40,41), HNF6 gene expression was appropriately increased in large (by 1.5-fold) and small BEC (by 1.7-fold) relative to PBS control (Fig. 6A).…”
Section: Effects Of Increasing In Vivo Hnf6 Expression On Target Genesupporting
confidence: 85%
See 2 more Smart Citations
“…6). As expected from our laboratory's previous work in GH-treated liver (40,41), HNF6 gene expression was appropriately increased in large (by 1.5-fold) and small BEC (by 1.7-fold) relative to PBS control (Fig. 6A).…”
Section: Effects Of Increasing In Vivo Hnf6 Expression On Target Genesupporting
confidence: 85%
“…With respect to ntcp, transient transfection of CMV-HNF6 expression vectors in HepG2 cell lines did not activate ntcp reporter gene constructs (data not shown). Furthermore, prior AdHNF6 liver infection by tail vein injection did not enhance whole liver ntcp or mrp2 expression (40), suggesting that ntcp and mrp2 gene response cannot be directly attributed to simple HNF6 transcriptional effects on their promoters. Since HNF commonly participate in a transcriptional network with the proper complement of HNF and cross-interaction among HNFs controlling the target gene profile, BEC upregulation of ntcp and mrp2 expression following AdHNF6 infection could be due to potential molecular synergistic interactions between HNF6 and HNF1a/HNF4a/Foxa2, perhaps through the recruitment of coactivators to orchestrate target gene activation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As conclusive evidence that FSH plays a key role in sustaining cholangiocyte proliferation by an autocrine mechanism, we have knocked down the FSH gene in NRICC and demonstrated that lack of FSH in cholangiocytes leads to loss of proliferative capacity and enhanced apoptosis. In support of the growth-promoting effects of FSH on the biliary epithelium, other studies have shown that other pituitary hormones, such as growth hormone (12,63) and prolactin (58), sustain cholangiocyte proliferation. Although FSH (expressed and secreted by hepatocytes) may modulate cholangiocyte growth by a paracrine mechanism, our studies support the novel concept that FSH is a key player in the autocrine loop regulating the balance between cholangiocyte proliferation and loss.…”
Section: Discussionmentioning
confidence: 92%
“…HNF6 controls the expression of many liver-specific genes, which are involved in the glucose metabolism, bile homeostasis, and hepatic cell proliferation (13). The expression of HNF6 is regulated by growth hormone (GH), and the GH-HNF6 pathway has been shown to be imperative for liver protection against chronic injury through regulating the expression of genes involved in proliferation (14)(15)(16). The GH-HNF6 pathway also contributes to the gender disparity via regulating the expression of some female-predominant genes (17).…”
mentioning
confidence: 99%